Romania : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Romania. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2022)
After a solid recovery from the pandemic, Romania is now, like other EU countries, facing strong headwinds related to the war in Ukraine. Output reached pre-crisis levels in H1 2021 and growth in Q1 2022 was strong. But inflation has risen rapidly, and the external and fiscal positions are weak. The authorities are implementing a support package of energy price caps and subsidies for vulnerable groups.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Romania